Estresse inicial e condicionamento ao baixo oxigênio no armazenamento em atmosfera controlada de maçãs "Royal Gala" - Both, Vanderlei (2012)
The aim of the present work was to evaluate alternative methods to conventional (CA) and dynamic controlled atmosphere (DCA), in order to maintain the quality of 'Royal Gala' apples, particularly the physical disorders occurrence. So, we evaluated the effect of initial low oxygen stress in maintaining the quality of 'Royal Gala' apples stored in ultralow oxygen conditions (less than 0.8 kPa) and also the effect of low oxygen conditioning through the gradual decreasing of oxygen in the storage chambers, and comparison of these techniques by applying 1-MCP. Two experiments were established, one in 2010 and another in 2011. At the first, the treatments were as follows: [1] CA with 1.2 kPa O2 + 2.0 kPa CO2; [2] 1.0 kPa O2 + 2.0 kPa CO2; [3] 0.8 kPa O2 + 1.0 kPa CO2; [4] 0.6 kPa O2 + 1.0 kPa CO2 e [5] 0.5 kPa O2 + 1.0 kPa CO2. For each CA treatment fruits were divided into two lots, one of them received 1-MCP application and another don´t. Then the fruits of each were again divided into two lots, and a portion was subjected to an initial low oxygen stress (0.3 kPa for seven days) and the other was enclosed in CA chambers. For the second experiment were used the following treatments: [1] CA with 1.0 kPa O2 immediately installed; [2] 1.0 kPa O2 and conditioning for seven days; [3] 0.8 kPa O2 and conditioning for seven days; [4] 0.7 kPa O2 and conditioning for seven days; [5] 0.7 kPa O2 and conditioning for 14 days; [6] 0.7 kPa O2 and conditioning for 28 days; [7] 0.5 kPa O2 and conditioning for seven days; [8] 0.5 kPa O2 and conditioning for 14 days; [9] 0.5 kPa O2 and conditioning for 28 days; [10] 0.7 kPa O2 with conditioning and low oxygen stress; [11] 1.0 kPa O2 immediately installed, plus 1-MCP and [12] DCA with chlorophyll fluorescence. For all treatments the partial pressure of CO2 was 1.2 kPa. The initial low oxygen stress increases the occurrence of physiological disorders, and shouldn t recommended for use immediately after harvest, however, after one low O2 adaptation period of the fruit, this procedure helps to maintaining quality during storage in ultralow oxygen conditions. The gradual reduction of O2 for approximately one month, allows storage in ultralow oxygen conditions and maintaining fruit quality better than the DCA. 1-MCP application offers low efficiency when the O2 concentration in the storage chambers are extremely low, or when the fruits presented an advanced maturity stage.